2021
DOI: 10.18203/2394-6040.ijcmph20213023
|View full text |Cite
|
Sign up to set email alerts
|

Burden of undernutrition among children of 12-59 months living in a slum of Kolkata: a cross-sectional study

Abstract: Background: Children living in slums are often deprived of good health. Their predisposition to malnutrition, makes them vulnerable to various infections and deficiency disorders affecting their growth. The objective of the study was to assess the nutritional status of 12-59 months children using Composite Index of Anthropometric Failure, to find out their morbidity profile, dietary diversity scores and to determine factors associated with CIAF.Methods: Study was conducted among 115 children of 12-59 months ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In 2018, 58.7% of Indonesian underfive children experienced nutritional problems, 17.7% were underweight, 30.8% stunting, and 10.2% wasting (3). Research in West Bengal, India, found that 59.1% of children experienced nutritional problems based on a conventional index (16.5% underweight, 27.8% stunting, and 14.8% wasting), while based on CIAF 43.5% of underfive children had anthropometry failure (4). The prevalence difference occurs because under-five children have more than one nutritional problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, 58.7% of Indonesian underfive children experienced nutritional problems, 17.7% were underweight, 30.8% stunting, and 10.2% wasting (3). Research in West Bengal, India, found that 59.1% of children experienced nutritional problems based on a conventional index (16.5% underweight, 27.8% stunting, and 14.8% wasting), while based on CIAF 43.5% of underfive children had anthropometry failure (4). The prevalence difference occurs because under-five children have more than one nutritional problem.…”
Section: Introductionmentioning
confidence: 99%
“…This condition can cause nutritional problems in under-five children. The unemployment rate, family income, living in rural areas, maternal education, gender, low diversity of food, infectious diseases, non-exclusive breastfeeding, birth weight, and birth length can affect the child's nutritional status (4,(10)(11)(12)(13)(14)(15)…”
Section: Introductionmentioning
confidence: 99%